2021
DOI: 10.3390/polym13142275
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Evaluation of Macrocrystalline and Nanocrystalline Cellulose as Potential Corrosion Inhibitors for SS316 Alloy during Acid Pickling Process: Experimental and Computational Methods

Abstract: Converting low-cost bio-plant residuals into high-value reusable nanomaterials such as microcrystalline cellulose is an important technological and environmental challenge. In this report, nanocrystalline cellulose (NCC) was prepared by acid hydrolysis of macrocrystalline cellulose (CEL). The newly synthesized nanomaterials were fully characterized using spectroscopic and microscopic techniques including FE-SEM, FT-IR, TEM, Raman spectroscopy, and BET surface area. Morphological portrayal showed the rod-shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Finally, the protection ability of the CeO 2 @gelatin molecule for the corrosion of the steel surface is associated with its molecular surface area. The corrosion prevention ability improved as the molecular area is augmented owing to the increase of the steel surface area covered with the inhibitor molecule [55]. As shown in Table 3, the CeO 2 @gelatin molecule had larger molecular surface area (3092.08 Å 2 ) than the CeO 2 and gelatin molecules, which reinforces the corrosion inhibition efficiency for the CeO 2 @gelatin molecule.…”
Section: Simulationsmentioning
confidence: 77%
“…Finally, the protection ability of the CeO 2 @gelatin molecule for the corrosion of the steel surface is associated with its molecular surface area. The corrosion prevention ability improved as the molecular area is augmented owing to the increase of the steel surface area covered with the inhibitor molecule [55]. As shown in Table 3, the CeO 2 @gelatin molecule had larger molecular surface area (3092.08 Å 2 ) than the CeO 2 and gelatin molecules, which reinforces the corrosion inhibition efficiency for the CeO 2 @gelatin molecule.…”
Section: Simulationsmentioning
confidence: 77%
“…Lastly, the protection proficiency of the CeO 2 -CMC molecule for corrosion of the MS surface is correlated with its molecular surface area. The corrosion protection capability improved as the molecular area was enhanced because of the increase in MS surface area shielded with adsorbed inhibitor molecules [ 79 ]. As shown in Table 3 , the CeO 2 -CMC molecule had a greater molecular surface area (2741.52 Å 2 ) than CeO 2 and CMC molecules, which boosts the corrosion protection proficiency of the CeO 2 -CMC molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Carbohydrate polymers have been advertised as a class of molecules that can protect metals from corrosion by acting as good inhibitors over other chemicals due to their inherent stability, the presence of multiple adsorption sites, availability, relatively lower cost, and environmentally friendly nature [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Corrosion inhibition by carbohydrate polymers has a unique inhibiting mechanism to counteract corrosion through adsorption on the surfaces of metals via specific centers of adsorption and through forming a shielding layer that protects it from aggressive environments.…”
Section: Introductionmentioning
confidence: 99%
“…The geometrical configuration and functional groups of these biopolymers are the main factors influencing their corrosion-inhibiting effects [ 29 ]. In light of the abovementioned facts, some research groups in recent decades reported that carbohydrate polymers were utilized as proficient corrosion inhibitors in diversity media [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Phosphorylated chitin was investigated as a corrosion inhibitor for steel in a neutral medium [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation